2021
DOI: 10.3390/educsci11100647
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Scientific Reasoning Skills among Pre-Service Science Teachers: A Latent Class Analysis

Abstract: We investigated the scientific reasoning competencies of pre-service science teachers (PSTs) using a multiple-choice assessment. This assessment targeted seven reasoning skills commonly associated with scientific investigation and scientific modeling. The sample consisted of 112 PSTs enrolled in a secondary teacher education program. A latent class (LC) analysis was conducted to evaluate if there are subgroups with distinct patterns of reasoning skills. The analysis revealed two subgroups, where LC1 (73% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…SR skills in the sophisticated group and DA skills in the experimental group are the features of those students, respectively. This finding is in line with Khan and Krell's (2021) study that groups revealed a superior skill among inquiry competencies regarding SR and associated skills. Nevertheless, an issue that emerges from these findings is that the inferiority of DA skills was conceded in the basic students.…”
Section: Discussionsupporting
confidence: 91%
“…SR skills in the sophisticated group and DA skills in the experimental group are the features of those students, respectively. This finding is in line with Khan and Krell's (2021) study that groups revealed a superior skill among inquiry competencies regarding SR and associated skills. Nevertheless, an issue that emerges from these findings is that the inferiority of DA skills was conceded in the basic students.…”
Section: Discussionsupporting
confidence: 91%
“…The global world is filled with anger, fear, misinformation, distrust and discouragement (Reis, 2021), especially during a pandemic. Global society should be modern science-and technology-based societies (Krell et al, 2022) and has strong scientific reasoning (Bicak et al, 2021;Hilfert-Rüppell et al, 2021;Khan & Krell, 2021;Mahler et al, 2021;Meister & Upmeier Zu Belzen, 2021;Rost & Knuuttila, 2022;Schellinger et al, 2021). COVID-19 pandemic has provided on disclosing the fact that most of the public science education and learning.…”
Section: Author's Nationality and International Collaborationmentioning
confidence: 99%
“…Others have broadened their scope and discuss aspects that are somewhat "on the sidelines" of what is typically considered scientific reasoning, such as the relevance of conceptual knowledge for reasoning in a specific context [40] and through reasoning on controversial science issues [41]. Most of the contributions address the abilities related to experimentation and modeling (e.g., [39,42,43]); this mirrors the focus of science education on these two styles of reasoning. However, this focus has been criticized as "an impoverished account" of scientific reasoning [9] (p. 17).…”
Section: Contributions In This Special Issuementioning
confidence: 99%
“…The approach of coding outlined in [39] indicates that scientific correctness is at the center of this conceptualization and not measurement repetition or error analysis, as it might have been in a physics approach. Another example is provided by Khan and Krell [42], who describe a two-dimensional competency-based approach to scientific reasoning (conducting scientific investigations and using scientific models) and also define sub-competencies of scientific reasoning and the associated abilities, including the necessary procedural and epistemic knowledge (based on [11]). They argue that the ability of generating hypotheses requires the knowledge that hypotheses are empirically testable, intersubjectively comprehensible, clear, logically consistent, and compatible with an underlying theory [42] (p. 3).…”
Section: Contributions In This Special Issuementioning
confidence: 99%
See 1 more Smart Citation